Clinical profile and outcome of Henoch Schonlein purpura in a tertiary care hospital in South India - Abbas, Shanavas; S., Geetha; R.V., Deepthi; Kamar, Jubin; Uthup, Susan (International Journal of Contemporary Pediatrics, 2017)
Background: Henoch Schonlein purpura (HSP) is the most common systemic vasculitis in children. It is an immunoglobulin A (IgA) mediated systemic small-vessel vasculitis, with IgA deposition in vessel walls leading to symptoms involving the skin, joints, intestines, and kidneys. The objective of present study was to identify and describe the clinical profile, pattern of joint involvement, histopathological features, treatment modalities and complications of Henoch Schonlein purpura. Methods: 52 children less than 12 years diagnosed to have Henoch Schonlein Purpura according to the European League against Rheumatism criteria were included in the study. All patients were subjected to detailed history taking and thorough examination. The clinical features, investigations, management and complications of the disease were studied. Descriptive statistics was used to analyse the results. Results: The common clinical features were palpable purpura (100%) followed by arthritis (66%) and abdominal pain (50%). Renal manifestations were in the form of hematuria in 12% of the patients. Skin biopsy was done in 25 patients of which 19 had findings suggestive of Henoch Schonlein purpura. Steroids were used in 42% of patients. The severity of illness was associated with lower mean age, arthritis, leg edema and stool occult blood. Conclusions: The clinical features of Henoch Schonlein purpura in the population were different from the previously published studies. Renal involvement was less common. The short-term outcome of the patients were satisfactory.